MENSINERGIKAN KAPASITAS DAN KAPABILITAS SATUAN POLISI PAMONG PRAJA PROVINSI KALIMANTAN BARAT DALAM MENGOPTIMALKAN TUPOKSI PERLINDUNGAN KEPADA MASYARAKAT - Marbun E.21110030 (FISIP Universitas Tanjungpura, 2014)
The entitled of this article “ the less Capacity and Capabilytas Status of Government Regulation Task And Function Principal Civil Service Police Unit West Kalimantan. Writing this article is intended to describe and analyze resource Municipal Police Units in the province of West Kalimantan Optimizing Community Auth Such protective yet effective. Aspects of the indicator to explain these phenomena is pernsonil, and facilities work.The conclusion of this research is less effective Cinergy Capacity and Capabilytas Status of Government Regulation Task And Function Principal Civil Service Police Unit West Kalimantan. It was influenced by resources factors. the resource availability of personnel resources seen is still lacking. Judging from the completeness of the supporting infrastructure is still lacking in the field of personnel. Keyword: Capacity and Capability Officer, Job Availability Means.